Nurse-led heart failure clinics improve survival and self-care behaviour in patients with heart failureResults from a prospective, randomised trial - Anna Strömberg (2003)
The aim of this trial was to prospectively evaluate the effect of follow-up at a nurse-led heart failure clinic on mortality, morbidity and self-care behaviour for patients hospitalised due to heart failure for 12 months after discharge.A total of 106 patients were randomly assigned to either follow-up at a nurse-led heart failure clinic or to usual care. The nurse-led heart failure clinic was staffed by specially educated and experienced cardiac nurses, delegated the responsibility for making protocol-led changes in medications. The first follow-up visit was 2-3 weeks after discharge. During the visit the nurse evaluated the heart failure status and the treatment, gave education about heart failure and social support to the patient and his family.There were fewer patients with events (death or admission) after 12 months in the intervention group compared to the control group (29 vs 40, p=0.03) and fewer deaths after 12 months (7 vs 20, p=0.005). The intervention group had fewer admissions (33 vs 56, p=0.047) and days in hospital (350 vs 592, p=0.045) during the first 3 months. After 12 months the intervention was associated with a 55% decrease in admissions/patient/month (0.18 vs 0.40, p=0.06) and fewer days in hospital/patient/month (1.4 vs 3.9, p=0.02). The intervention group had significantly higher self-care scores at 3 and 12 months compared to the control group (p=0.02 and p=0.01).Follow up after hospitalisation at a nurse-led heart failure clinic can improve survival and self-care behaviour in patients with heart failure as well as reduce the number of events, readmissions and days in hospital.